Cross-species chromosome painting offers new insights into the phylogenetic relationships among 16 representative species of Ipomoeeae - Sun, Jianying; Chen, Lei; Sun, Jian; Li, Zongyun; Han, Yonghua (Frontiers in Plant Science, 2025)
IntroductionPrevious phylogenetic studies of Ipomoeeae species have shown inconsistent results, and latest molecular analyses have classified this tribe into two major clades (Argyreiinae and Astripomoeinae) comprising seven smaller clades. The cross-species chromosome painting (CCP) analysis can offer valuable insights into the phylogenetic relationships among species.MethodsHere, we analyzed representative species from each small clade using CCP with oligonucleotide (oligo) probes derived from chromosomes 7 (7-1/7-2) and 15 (15-1/15-2) of Ipomoea nil to further elucidate their phylogenetic relationships.Results and discussionWe found that each probe produced specific hybridization signals exclusively on one chromosome pair in all analyzed species, suggesting that the synteny of two chromosomes have been maintained after nearly 25 million years of divergence of these species. Despite conserved synteny, distinct chromosome painting patterns were observed among species. In all analyzed 2n=30 species from Astripomoeinae clade, probes of 7-1/7-2 and 15-1/15-2 hybridized to opposite chromosomal arms of their homologous chromosomes, respectively. By contrast, 2n=30 species from Argyreiinae showed co-localization of 7-1 and major 7-2 signals on same chromosomal arm along with weaker 7-2 signals on the opposing arm, while maintaining the 15-1 and 15-2 probes to different chromosomal arms. Notably, in all analyzed 2n=28 species from two major clades, two probes from the same chromosome showed co-localization to the same chromosomal arm, indicating that inter-chromosomal translocations or rearrangements have involved these two chromosomes. Thus, CCP analysis revealed significant cytogenetic divergence between 2n=28 and 2n=30 species that challenges existing molecular-based classifications which cluster them within the same small clade. Additionally, species relationships were further resolved through physical mapping of the 5S and 45S rDNA using fluorescence in situ hybridization (FISH), which revealed significant interspecific variation in rDNA distribution patterns, enabling the differentiation of most species from the same clade with indistinguishable chromosome painting patterns.